Computational Study on the Thermal Decomposition of Phenol‐Type Monolignols. Issue 4 (22nd February 2018) - Furutani, Yuki; Dohara, Yuki; Kudo, Shinji; Hayashi, Jun‐Ichiro; Norinaga, Koyo
ABSTRACT: A detailed chemical kinetic model has been developed to theoretically predict the pyrolysis behavior of phenol‐type monolignol compounds (1‐(4‐hydroxyphenyl)prop‐2‐en‐1‐one, HPP; p ‐coumaryl alcohol, 3‐hydroxy‐1‐(4‐hydroxyphenyl)propan‐1‐one, HHPP; 1‐(4‐hydroxyphenyl)propane‐1, 3‐diol, HPPD) released from the primary heterogeneous pyrolysis of lignin. The possible thermal decomposition pathways involving unimolecular decomposition, H‐addition, and H‐abstraction by H and CH3 radicals were investigated by comparing the activation energies calculated at the M06–2X/6–311++G(d, p) level of theory. The results indicated that all phenol‐type monolignol compounds convert to phenol by side‐chain cleavage. p ‐Coumaryl alcohol decomposes into phenol via the formation of 4‐vinylphenol, whereas HPP, HHPP, and HPPD decompose into phenol via the formation of 4‐hydroxybenzaldehyde. The pyrolytic pathways focusing on the reactivity of the hydroxyl group in HPP and producing cyclopentadiene ( cyc ‐C5 H6 ) were also investigated. The transition state theory (TST) rate constants for all the proposed elementary reaction channels were calculated at the high‐pressure limit in the temperature range of 300–1500 K. The kinetic analysis predicted the two favorable unimolecular decomposition pathways in HPP: the one is the dominant channel below 1000 K to produce cyc ‐C5 H6, and the other is above 1000 K to yield phenol (C6 H5 OH).